Involvement of alpha2 and beta2-adrenoceptors on breast cancer cell proliferation and tumour growth regulation - Perez, Cecilia (2012)
Background and purpose: Beta-adrenoceptor (B-AR) expression is known in human and experimental animal breast cancer cells. However, the effect of the agonists and antagonists reported on cell proliferation and tumour growth was paradoxical, precluding the utilization as possible adjuvant therapy, mainly in the cases of refractory tumours. Experimental approach: The expression of B-AR was analysed by immunofluorescence and RT-PCR. Cell proliferation was assessed by [(3) H]-thymidine incorporation, tumour growth by measuring with a calliper and Erk 1/2 phosphorylation by western blotting. Key results: B2 -AR expression was confirmed in the mouse and human cells tested. Cell proliferation was increased by epinephrine (by alpha(2)-AR action) and decreased in every tested cell line by the B-agonist isoproterenol and the B2-agonist salbutamol. Isoproterenol and salbutamol reduced tumour growth in every tumour tested (mouse C4-HD and CC4-3-HI and human IBH-4, IBH-6 and MDA-MB-231 cell lines growing as xenografts in nude mice). This effect was reversed by the B-adrenergic antagonist propranolol. The alpha2-adrenergic antagonist rauwolscine and the B2-adrenergic agonist salbutamol performed equally well in diminishing tumour growth. Erk 1/2 activation analysed in IBH-4 tumours perfectly matched tumour growth, with the B-adrenergic agonists lowering its activation. Erk 1/2 phosphorylation inhibition in vitro was mainly mediated by the PKA pathway. Conclusions and Implications: In the experimental models studied, the B-adrenergic agonists inhibit breast cancer cell proliferation and tumour growth. This effect is probably mediated by Erk 1/2 phosphorylation inhibition. The B-adrenergic agonists perform equally well as the alpha2-adrenergic antagonist rauwolscine, providing possible novel therapeutic adjuvant treatments for breast cancer.